Tax attractiveness and the location of patents - Andreas Dinkel; Deborah Schanz (Arbeitskreis Quantitative Steuerlehre (arqus), 2015)
This paper analyzes the impact of taxation on the location of patents within multinational groups. Based on groups with parents from 36 countries globally and their patent holdings in 36 European countries, we provide insight into the determinants of three subsequent decisions: (1) the decision of whether to locate patents abroad; (2) in which countries to locate patents; and (3) how many patents to locate in each country. Our findings indicate that multinationals take the tax attractiveness of countries into account when making these decisions. Specifically, we show that the statutory tax rate, the taxation of royalties, R&D incentives, and transfer pricing rules help to explain the patent-location choices of multinationals.
Keywords: H25; H73; F23; 330; International taxation; Tax attractiveness; Intellectual property; Location decision; Multinational enterprise